2011
DOI: 10.1007/s12020-011-9540-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of insulin resistance and impaired glucose tolerance in a sample of obese spanish children and adolescents

Abstract: The prevalence of obesity in children has increased in developed countries in the last decades. It is associated with alterations in glucose metabolism that may be present in childhood. To assess the frequency of glucose metabolism alterations and insulin resistance and their possible determinants in a sample of obese children from Valladolid (Spain), we retrospectively studied 100 obese children and adolescents (11.59 ± 2.73 years). Anthropometric measures, biochemical parameters, and oral glucose tolerance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 26 publications
1
13
0
6
Order By: Relevance
“…Thus, we could consider a limitation in our study not having included a group of patients with type 2 diabetes in the analysis. However, the current prevalence of type 2 diabetes in our Caucasian youth population is very low [24, 25]. Therefore, it is unlikely that MODY may be misdiagnosed as type 2 diabetes in this pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we could consider a limitation in our study not having included a group of patients with type 2 diabetes in the analysis. However, the current prevalence of type 2 diabetes in our Caucasian youth population is very low [24, 25]. Therefore, it is unlikely that MODY may be misdiagnosed as type 2 diabetes in this pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of IR is increasing worldwide [2831]. Studies have indicated that IR was significantly associated with ApoB/ApoA-I ratio, metabolic syndrome (MetS), and lipid indices.…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear whether the same cutoffs should apply to youth, and whether mild elevations during the increased insulin resistance of puberty will persist [41 ▪ ,52,53 ▪ ,54,55 ▪ ]. Both fasting and OGTT-based measures can be problematic for early diagnosis [17 ▪▪ ,26,56 ▪ ,57 ▪ ,58,59], HbA1c and OGTT values are poorly correlated [41 ▪ ], repeated OGTT’s have poor reproducibility in youth [60] and HbA1 can vary substantially depending on method, making diagnosis of prediabetes and early T2DM difficult. One recent proposal was to conduct OGTTs in children with a HbA1c more than 5.5% [61], whereas others recently proposed an algorithm including glucose, triglycerides and BMI; HbA1c did not add to the predictive value of this method [62 ▪▪ ].…”
Section: Prevalence and Diagnosis Of Pediatric Type 2 Diabetes Mellitusmentioning
confidence: 99%